2013
DOI: 10.1177/0148607113513801
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing Glutamine Concentration Causes Mitochondrial Uncoupling in an In Vitro Model of Human Skeletal Muscle

Abstract: Glutamine concentrations, consistent with moderate clinical hypoglutaminemia (300 µM), bring about an optimal condition of myoblast proliferation and for efficiency of aerobic phosphorylation in an in vitro model of human skeletal muscle. These data support the hypothesis of hypoglutaminemia as an adaptive phenomenon in conditions leading to bioenergetic failure (eg, critical illness).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The effect of hyper glutamine levels on inflammatory mediator and HSP70 release during sepsis is also unknown. In in vitro models, high levels of glutamine supplementation (5 mM) resulted in respiratory uncoupling and energy wasting within the mitochondria and were associated with cell death [55]. Therefore, caution is required when translating results from experimental work particularly in septic shock models to inform clinical practice, especially as results from recent large clinical trials questioned the benefits of glutamine supplementation in adults with septic shock with multiorgan failure [53].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hyper glutamine levels on inflammatory mediator and HSP70 release during sepsis is also unknown. In in vitro models, high levels of glutamine supplementation (5 mM) resulted in respiratory uncoupling and energy wasting within the mitochondria and were associated with cell death [55]. Therefore, caution is required when translating results from experimental work particularly in septic shock models to inform clinical practice, especially as results from recent large clinical trials questioned the benefits of glutamine supplementation in adults with septic shock with multiorgan failure [53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Krajcova et al have suggested the hypoglutaminaemia seen during critical illness may be a protective mechanism. They show that supra physiological levels of glutamine decrease the efficiency of the mitochondrial respiratory chain contributing to the bioenergetics failure of the mitochondria (a feature of critical illness), where engorged mitochondria are not able to meet adenosine tri phosphate demands of tissues, resulting in cell death [61]. As such the hypoglutaminaemia described by us [23] and others during critical illness [62], may be a protective mechanism decreasing mitochondrial size allowing for restoration and repair during the recovery phase [61].…”
Section: LV Marino Et Al / Clinical Nutrition Xxx (2014) 1e7mentioning
confidence: 99%
“…The mechanism for the effect of supra physiological glutamine levels on HSP70 release and inflammatory mediators in critical illness is not known. However, an in vitro model of human skeletal muscle linked supraphysiological levels of glutamine to respiratory uncoupling and energy wasting within the mitochondria which was associated with cell death [61]. In addition, Krajcova et al have suggested the hypoglutaminaemia seen during critical illness may be a protective mechanism.…”
Section: LV Marino Et Al / Clinical Nutrition Xxx (2014) 1e7mentioning
confidence: 99%
“…Such small samples allow for the measurement of activities of individual complexes of respiratory chain by spectrophotometry [Pecinová et al, 2011;Votion et al, 2012;Pesta and Gnaiger, 2012] or their concentration by blotting techniques [Wittig et al, 2007;Nabben et al, 2011;Smith et al, 2014]. Protocols for functional assessment of mitochondrial function based on measurement of O 2 consumption are developed for isolated mitochondria [Chance and Williams, 1956], permeabilised muscle fibres [Saks et al, 1998 Jul] or for the use of human cultured myoblasts [Krajcova et al, 2015]. The yield during mitochondria isolation is low (20-40% [Tonkonogi and Sahlin, 1997]) and isolated mitochondria may not represent the whole mitochondrial population in a cell, potentially introducing bias [Palmer et al, 1985;Ferreira et al, 2010;Picard et al, 2010].…”
Section: Introductionmentioning
confidence: 99%